Evaluation of effect of local exogenous application of Myrrh oil on healing of wound incisions of facial skin (Histochemical, Histological and Histomorphometrical study in rabbits) - Nawar Bahjet Kamil; Nada M. Al-Ghaban (College of Dentistry/ University of Baghdad, 2019)
Aim of the study: Is to evaluate the effect of myrrh oil local application on the healing process of skin wounds histologically , histomorphometrically and , histochemically. Materials and methods:Twenty male white New Zealand rabbits were used in this study. An incisional wounds with full thickness depth and of 2 cm length were done on both sides of the cheek skin of each rabbit. The left sided incisions (the control group) were irrigated with distilled water (10µL). The right sided incisions (the experimental groups) were treated with myrrh oil (10µL). Each group was subdivided into 4 subgroups according to the healing interval into 1,3,7 and 14 days(5 rabbits for each group). Results: Histological findings of our current study showed a highly significant difference between the experimental and the control groups in count of the inflammatory cells which showed that mean values increased with time for the control and the experimental groups. The histomorphometrical findings had shown that the thickness of the epithelium was nearly completed at about 7 days for the experimental groups and at about 14 days for the control. The blood vessels count was recorded to have a highly significant difference between the groups at days 1 and 3 only. The histochemical findings had shown that the collagen fibers remodeling had recorded a highly significant difference between the control and the experimental groups at days 7 and 14. Conclusion: The current study had revealed that myrrh oil accelerates wounds healing in rabbits. Key word:Wound healing , Myrrh oil, Masson's Trichrome staining.